THERMAL IMAGING SURVEY – THERMAL IMAGING PHOTOGRAPHY OF BUILDINGS AND STRUCTURES - Jobborov , Baxodir Tulqinjon ugli (Educational Research in Universal Sciences, 2023)
Currently, along with an increase in construction volumes, the requirements for the quality and comfort of constructed facilities are increasing. New architectural solutions are increasingly being used using modern (innovative) building materials with completely different properties, in contrast to traditional materials. In this regard, quality control of completed installation work is a labor-intensive process and is often not carried out in full and with due attention.